Analisis Perilaku Konsumen terhadap Keputusan Pembelian Buah-Buahan di Moena Fresh Bali - NI MADE SRI KESARI DHARMA PADMI; RATNA KOMALA DEWI; I.G.A.A. LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Analysis of Consumers’ Behavior Against The Decision on PurchasingFruits in Moena Fresh This research aimed to (1) analyze the process of decision making in purchasing freshfruits in Moena Fresh, (2) analyze the factors which influence the consumers indeciding to purchase fruits in Moena Fresh. The data analysis method that wereused were descriptive analysis to find out the process of decision making inpurchasing the fruits and factor analysis to analyze the factors which influenced theconsumers in deciding to purchase the fruits in Moena Fresh.The results showed some of the steps that consumer passing through beforepurchasing, those were the recognition of needs, search of information, evaluation ofalternatives, purchase, and post-purchase. Factors that influenced the consumers indeciding the purchasing of fresh fruits in Moena Fresh include external factor andinternal factor. External factor that is environment factor that involves variable offreshness of the fruits, fruit hygiene, packaging, price of fruits, cleanliness of therack, service of the store employees, store temperature, and the aroma of the store.Internal factor that is psychological factor that involves variable of the types of thefruits; and also individual differences factor consists of the income of the consumers.Suggestions that can be given that Moena Fresh pay attention to the availality of fruiton order to avoid a product void and consider other factors such as, advertising andsituation of consumer psychology.